Optimal Blood Concentration of Cyclosporine Among Iranian Kidney Transplant Recipients (Iranian Journal of Kidney Diseases, 2012)
Introduction. Clinical information concerning cyclosporine dose reduction in Iranian kidney transplant recipients is limited. There are data in Asian, Caucasian, and Iranian ethnic kidney transplant recipients that recommend the trough level (C0) and 2-hour postdose level (C2) of cyclosporine may be different. Our aim was to determine therapeutic levels of C0 and C2 at different time after transplantation among Iranian transplant patients. Materials and Methods. Blood concentrations of cyclosporine were assessed in 4419 samples of kidney transplant recipients between 2008 and 2010. The patients were divided into 3 groups according to the time of laboratory studies (< 3 months, 4 to 12 months, and > 1 year after transplantation). Both univariable and multivariable analyses were performed to determine the correlation between cyclosporine blood levels and serum creatinine. Results. A total of 1270 kidney transplant patients with 4419 blood samples enrolled. The mean age of the donor was 28 ± 6 years (range, 6 to 64 years) and 82.6% were men and 17.4% were women. In the subset of patients with serum creatinine values of at least 1.6 mg/dL for men and 1.4 mg/dL for women, we determined C0 and C2 levels between therapeutic and undertherapeutic creatinine ranges at 3 different time interval after transplantation, as follows: the first 3 months, 230 ng/mL to 240 ng/mL and 725 ng/mL to 775 ng/mL; 4 to 12 months, 135 ng/mL to 156 ng/mL and 535 ng/mL to 612 ng/mL; and after 1 year, 95 ng/mL to 120 ng/mL and 420 ng/mL to 479 ng/mL for C0 and C2, respectively. Conclusions. The present study suggests that the cyclosporine levels for Iranian kidney transplant patients are lower compared to the recommended levels in western countries.